ANALISIS PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP HARGA SAHAM (Studi Pada Perusahaan KOMPAS100 Periode 2018-2020) - Erwin Febriansyah; Tiara Pratama; Fadrul (Realible Accounting Journal, 2023)
This study aimed to determine the effect of corporate social responsibility disclosures consisting of CSR-Economic, CSR-environmental, and CSR-social disclosures in companies included in the KOMPAS100 index on the Stock Exchange. The population of this study amounted to 100 companies, conducted a sample selection by using purposive sampling technique. The sample was24 companiesthat selected by certain considerations. The data collection techniques was obtained through documents of the website (www.idx.co.id) and the official website of each company. The data were analyzed by using the Ttest and F test. The research results show that (1) CSR-Economy as measured by CSRDI-Economy in the disclosure of corporate social responsibility has a significant effect on stock prices (2) CSR-Environment as measured by CSRDI-Environment in the disclosure of Corporate Social Responsibility does not have a significant effect on stock prices, (3) CSR-Social as measured by CSRDI-Social in the disclosure of Corporate Social Responsibility has no significant effect on stock prices, (4) and simultaneous disclosure has no significant effect on stock prices. Keywords: Stock Price, Corporate Social Responsibility, CSR-Economy, CSR Environment, and CSR-Social.